2004
DOI: 10.1302/0301-620x.86b5.13549
|View full text |Cite
|
Sign up to set email alerts
|

Glenohumeral arthrodesis in upper and total brachial plexus palsy

Abstract: We have compared the functional outcome after glenohumeral fusion for the sequelae of trauma to the brachial plexus between two groups of adult patients reviewed after a mean interval of 70 months. Group A (11 patients) had upper palsy with a functional hand and group B (16 patients) total palsy with a flail hand. All 27 patients had recovered active elbow flexion against resistance before shoulder fusion. Both groups showed increased functional capabilities after glenohumeral arthrodesis and a flail hand did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 12 publications
1
51
0
1
Order By: Relevance
“…14 This study found that the type of bone graft significantly influenced outcomes, with a massive corticocancellous bone graft having significantly higher fusion rates (P Ͻ .001). This study compared cancellous versus corticocancellous graft.…”
Section: Discussionmentioning
confidence: 71%
“…14 This study found that the type of bone graft significantly influenced outcomes, with a massive corticocancellous bone graft having significantly higher fusion rates (P Ͻ .001). This study compared cancellous versus corticocancellous graft.…”
Section: Discussionmentioning
confidence: 71%
“…Shoulder outcome in terms of functional range may not be as good after glenohumeral arthrodesis as that seen after neurotisation from C5/C6 or the contralateral C7 [2]. Although glenohumeral arthrodesis may be seen as an acceptance of failure of the primary nerve repair, it clearly has a place in the management of complete lesions to provide stability, particularly where scapulothoracic musculature is preserved [3,4]. Glenohumeral fusion was carried out prior to the biceps transfer in two patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, however, it was demonstrated that previous harvesting of the spinal accessory nerve did not interfere with range of abduction or external rotation recovery following shoulder arthrodesis. 2 Chammas et al 11 performed shoulder arthrodesis in 27 patients with brachial plexus palsy and identified no differences relating to whether the spinal accessory nerve had previously been transferred or the serratus anterior was paralyzed. They did find differences in the range of recovery of shoulder abduction depending on whether the upper portion of the pectoralis major was functional or paralyzed.…”
Section: Discussionmentioning
confidence: 99%